Applying Manual Pressure before Benzathine Penicillin Injection for Rheumatic Fever Prophylaxis Reduces Pain in Children - EMRE YAVUZ, DERYA (ELSEVIER SCIENCE INC, 2015)
The purpose of this study was to evaluate the efficacy of applying manual pressure before benzathine penicillin injection and compare it with the standard injection technique in terms of reducing discomfort in children with rheumatic heart disease grouped by age and gender. This was a single-blind, randomized, crossover study. Fifty-one patients aged 7.1-19.9 years were recruited for this study carried out in the pediatric cardiology outpatient clinic. Twenty-nine were girls (56.9%). All subjects received an intramuscular injection of benzathine penicillin with manual pressure to one buttock or with the standard technique to the other buttock at 3-week intervals. The two techniques were used randomly. The subjects were blinded to the injection technique and a visual analogue scale was used after the procedure. Findings demonstrate that children experienced significantly less pain when they received injections with manual pressure (1.3 +/- 0.9) compared with the standard injection (4.4 +/- 1.6) technique. The perceived injection pain was negatively related to the age of the children in both techniques. Compared with boys, girls felt more pain, but the difference between each technique group according to gender was negligible. The application of manual pressure reduces pain in children under the stress of repeated intramuscular injections, which supports the suggestion that it should be used in routine practice. Manual pressure to the injection site is a simple, pain-reducing technique. Implementing this technique in routine practice may also promote adherence to the prophylaxis regimen, especially in children. (C) 2015 by the American Society for Pain Management Nursing
Keywords: GATE CONTROL-THEORY; STREPTOCOCCAL PHARYNGITIS; INTRAMUSCULAR INJECTION; GENDER